Microbiological Findings and Clinical Outcomes in Ugandan Patients with Infected Burn Wounds - Johannes Weinreich; Christina Namatovu; Sara Nsibirwa; Leah Mbabazi; Henry Kajumbula; Nadine Dietze; Christoph Lübbert; Hawah Nabajja; Joseph Musaazi; Charles Kabugo; Amrei von Braun (MDPI AG, 2023)
Nosocomial wound infections are a dreaded complication in patients with burns. However, access to the necessary microbiological diagnostics is impaired in low-resource settings. This prospective observational cohort study aimed to describe the bacterial pathogens, resistance profiles and clinical outcomes of patients with wound infections admitted to the largest specialized unit for burns and plastic surgery in Uganda. Blood and wound swab cultures were taken for bacterial species identification and antibiotic susceptibility testing. A total of 140 patients (female: n = 62, 44.3%) with a median age of 26 (IQR 7-35) years were included between October 2020 and April 2022, of which the majority (n = 101, 72.2%) had burn wounds (72.3% Grade 2b, 14.9% Grade 3). Gram-negative Enterobacterales, Pseudomonas spp. and Acinetobacter spp. were most commonly isolated from wound swabs and nearly all isolates were multidrug resistant with very limited treatment options. While the clinical outcome was favorable in 21 (15%) study participants, the majority were left with disabilities (minor: n = 41, 29.3%, moderate: n = 52, 37%, major: n = 14 (10%)). Twelve (8.6%) study participants died, mostly of Gram-negative sepsis. Our findings highlight the urgent need for routine access to microbiological diagnostics to improve patient care and local surveillance efforts on antimicrobial resistance.